Development of herbal selection criteria model for investment and commercialization decision - Zakaria, Mohd Hafizudin (2016)
The National Key Economic Area (NKEA) has identified the herbal industry as one of the high value commodities to be further developed in both the production and processing sectors. Various government programs have been implemented to enhance the local herbal industry In Malaysia through the First Entry Point Projects (EPP1). Under NKEA, five herbs have been identified and proposed for commercialization in the industry: Tongkat Ali (Eurycoma longifolia), Kacip Fatimah (Labisia pumila), Dokong Anak (Phyllanthus niruri), Misai Kucing (Orthosiphon stamineus, Benth) and Hempedu Bumi (Andrographis paniculata). The selection of these herbs was made based on their discovery, agronomy, product development and both pre-clinical and clinical tests undertaken by policy makers and researchers. However, the selection criteria for investors should also consider other criteria such as the economic factors, environment, markets and government policies. Since such selection criteria are currently unavailable, there is a necessity for them to be identified and developed. It is also crucial to identify the order of importance of the identified criteria. The ranking of the criteria will provide an important guide in herbal selection for the decision making process by investors and policy makers. The main objective of this study is to develop the selection criteria for the commercialization of herbs and for investment decision making. This research served as a complement to the current criteria already established by policy makers. The criteria model developed will provide a helpful policy making tool which includes research, economic, environmental and other factors. This study used primary data which were obtained using purposive sampling whereby the involvement of respondents toward the herbal industry was taken into consideration. Data collection involved three phases of interviews. First, to elicit criteria constructs using the Decision Delphi technique which involved six respondents. The Second phase was carried out by a survey which involved 220 respondents. Finally, the third stage was to rank the herbs identified by the NKEA using the developed criteria in the second phase through a pairwise comparison technique or the Analytic Hierarchy Process (AHP) involving 12 respondents. The respondents for all phases were taken from four different backgrounds consisting of decision makers, researchers, entrepreneurs and herb cultivators. All the survey processes were carried out by face to face interviews, by telephone and by an online questionnaire using both the openended and close-ended structure. Results from the Decision Delphi Method revealed that there were 29 items of herbal selection criteria identified by all experts. All these items were combined with the criteria from various literatures, and they were then grouped into six main components using the Exploratory Factor Analysis (EFA). The analysis of Analytical Hierarchy Process indicated that the most important selection criterion is “Incentive and Assistance” followed by “Community Welfare” and “Marketability”. Other criteria such as “Research and Development”, “Economic” and “Policy and Regulation” were respectively ranked fourth, fifth and sixth. This meant that incentives and assistance were the most important criteria to encourage entrepreneurs or cultivators for the manufacture of their products. At the same time, these criteria acted as a backbone or a strong supporting factor for researchers to carry out their research in the herbal cluster supported by research grants, awards, promotions, incentives, royalties and others. The outcomes of this study could be considered as futher guideline for decision makers to identify herbs which are to be addressed by the government in the development of strategies to introduce the country’s flagship herbs that will give high returns to the national economy. Other than that, the criteria model that developed will provide a useful decision making tool for herbal entrepreneurs in selecting the most suitable herbs to be cultivated or processed and also could be extend to other crops.